Paediatric admissions at a tertiary Hospital in Kuala Lumpur-a case for a short-stay ward - Chong, L.A.; Lee, Way Seah; Goh, A.Y.T. (Malaysian Medical Association, 2003)
The profile of admissions staying less than 24 hours admitted to the paediatric wards of University Malaya Medical Center, Kuala Lumpur, over a period of six weeks was reviewed to ascertain the need of a short-stay ward. Ninety-three (22) of the 428 admissions admitted during the study period were discharged within 24 hours, 56 (60) were discharged within 12 hours. Major categories of admissions were: elective investigative procedures (43), and emergency admissions (44). Reasons for emergency admissions: infections 42, minor trauma/cerebral concussion 25 and febrile/afebrile seizures 11. Only 20 required percutaneous oximetry monitoring and 2 required observations more frequently than 2 hourly. There may be a case for a short stay ward in a big paediatric unit in Malaysia.